“ESG score” vs. “ESG rating”: a conceptual model for the sustainability assessment and self-assessment of European SMEs - Murè, Pina; Giorgio, Saverio; Antonelli, Valeria; Crisafulli, Antonino (Frontiers in Environmental Economics, 2024)
The paper presents a conceptual model, which materializes in the development of a questionnaire, useful for analyzing the technical-organizational determinants that facilitate the sustainability transition of small and medium-sized enterprises (also “SMEs”). This model aims to facilitate access to green and social financing offered by banks, and to optimize relationships with the supply chain leaders in a sustainable supply chain logic and in line with the new European Union (also “EU”) regulations. Considering the lack of scoring and rating systems focused on SME’s, the lack of direct normative for their sustainability transition and their simplified governance structure, a questionnaire was developed. This instrument serves to highlight SME’s strengths and weaknesses in the transition process and their related needs, and to underline the actions to enhance the sustainability transition to facilitate their self-assessment. For banks the questionnaire is a tool to assess the sustainability of their customers and redefine the offer of green and social credit products with respect to the needs of SMEs; supply chain leaders to ensure a sustainable supply chain, assess and support SMEs in their sustainability transition. The questionnaire is the result of the modification of the one used by a data provider to determine an Environmental (E), Social (S) and Governance (G) (also “ESG”) Score which does not reflect the peculiarities of SMEs. The proposed questionnaire, instead, can be used to obtain an ESG Score coherent with the characteristics of SMEs and adopts a forward-looking approach, proposing actions for the E, S and G to enhance the sustainability transition. It is composed of 31 questions: 5 in the preliminary analysis section; 13 Governance questions that assess SMEs' ability to establish strategies, organizational structures and policies for their sustainability transition; 7 Social questions that aim to examine the management of social responsibilities; 8 Environmental questions that assess the corporate policies and practices adopted by SMEs regarding environmental management. The questionnaire is currently being tested, administered to SMEs customers of a local bank and to SMEs that are suppliers of a supply chain, and may be modified based on the responses received.